Finance and Output Volatity During The Global Financial Crisis - Ibrahim, Mansor H.; Law, Siong Hook; Sukmana, Raditya (Muslim Business and Economics Review, 2024)
This paper assesses the effectiveness of financial depth and financial inclusion in the mitigation of output volatility during the 2008-2010 Global Financial Crisis. The paper also evaluates whether finance is more effective in countries with more developed financial systems, higher levels of economic developments, sounder banking systems, and better political stability. Employing a cross-sectional dataset covering more than 100 countries, our results indicate the ability of finance in subduing output volatility during the crisis. Our evidence is also concrete in suggesting the success of finance in reducing output volatility in more financially developed, advanced, and politically stable countries. However, the evidence is unclear on whether finance is beneficial for countries characterized by low, intermediate, or high banking stability. In addition to these findings, the preponderance of evidence tends to suggest the better ability of financial usage as compared to financial access in mitigating aggregate fluctuations during the crisis. Finally, our additional analysis reveals that finance functions well in stabilizing output when output volatility is high.